The Reorientation of Thailand’s National R&D Programmes - Limits and Challenges - Anittha Jutarosaga; Yupadee Hengjan; Santi Charoenpornpattana; Kommate Jitvanichphaibool (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
Since 2016 Thailand has recognised a significant transition in research and innovation policy, with government increasingly acknowledging the importance of national R&D programmes and favourable institutional conditions as determinants to overcome middle income trap. Drawing a lesson-learned from successful experiences of South Korea and Japan, the Thai government decided to experiment the national large-scaled mission-oriented R&D programme, known as ‘Spearhead R&D Programme’. This novel innovation financing scheme was designed to accelerate the commercialisation and economic impact of R&D outputs. From the outset, it was clear that the outcome and impact of Spearhead R&D Programme was yet to be realized. The purpose of this paper is to investigate the reorientation of Thailand’s research and innovation landscape with the focus on the efficiency of operation in relation to the objective of the Spearhead R&D Programme. It is found that the Spearhead R&D Programme is equipped with four novel conceptual and operational features including strategic national STI agenda, R&D commercialization, multi-year budget allocation and proactive research management. Yet, there were also potential limits and challenges that need to be addressed to move the Programme towards greater sectoral contribution with open innovation and flexibility in policy learning. Keywords: Research & Innovation Reform, Mission-oriented R&D Programme, Policy Experiment, Catch-up, R&D Commercialisation, Thailand